Development Opportunities, Support and Organizational Commitment: Career Success as a Mediator for Millennial Corporate Workers - Alessandro Senewe, Andrew Marcelo; Satrya, Aryana (Green Publisher Indonesia, 2025)
Millennial workers, who make up a significant portion of Jakarta’s corporate workforce, increasingly prioritize career success, growth, and support in their work. This research explores the impact of Perceived Opportunities for Competency Development (POCD) and Organizational Support for Career Development (OSCD) on Organizational Commitment (OC), with Subjective Career Success (SCS) acting as a mediating variable. Using a quantitative explanatory approach, data were collected from Millennial corporate employees in Jakarta with at least three years of work experience who have experienced some form of subjective career success. Structural Equation Modelling (SEM) was employed to examine the relationships among the variables. The findings indicate OSCD and SCS have a significant and positive impact on the organizational commitment of Millennial Corporate Workers in Jakarta, while POCD was found to have the opposite effect. However, SCS acts as a partial mediator for OSCD and OC and also exhibits a competitive mediation effect on the relationship between POCD and OC. These findings provide critical implications for organizations in developing effective HR strategies to retain Millennial talent, optimize career development programs, and enhance organizational commitment through strategic career support mechanisms.